(untitled) (Eurasian Journal of Ecology, 2016)
From the rhizosphere and rizoplana of healthy sugar beets, culture 43 cellulolytic bacteria were isolated. 12 strains that have expressed antagonism against phytopathogenic fungi of the genus Fusarium, causing root rot and seedling of sugar beet, were selected. Selected two strains of cellulolytic bacteria, characterized a high antifungal activity and the growth promoting of beets. Field tests have shown great promise strains use. Inoculation seeds of the cellulolytic bacteria infestation of fusariosus seedling decreased by 2,0-2,4 times, and the prevalence of root crops - 2,5-3,0 times as compared with the control and increase sugar beet harvest amounted to 30-34 kg/ha.